Service Quality Improvement Strategy in The Auto Insurance Industry: Customer Perspective Study - Andriani, Debrina Puspita (International Journal of Integrated Engineering, 2023)
Service quality is one of the parameters of conformity between consumers' perceived and expected services and influences the company's sustainability. In an insurance company, quality service is essential because advising quality services is important to develop more trusted engagement with the whole customers. In this study, the analysis of quality services was performed using gap analysis and quality function deployment (QFD) in auto insurance companies with intense competition. Gap analysis is required to identify the quality dimensions to be improved. While technical improvement actions are generated using the QFD method by mapping consumer needs and technical actions through the house of quality (HOQ) matrix. The results showed that using the integration of gap analysis and QFD, the auto insurance company received the gap scores and obtained recommendations for technical actions that could be adopted for continuous improvement.